Amplitude‐integrated electroencephalography shows mild delays in electrocortical activity in preterm infants born small for gestational age. (27th March 2015) - Griesmaier, E; Burger, C; Ralser, E; Neubauer, V; Kiechl‐Kohlendorfer, U
Abstract Aim Being born small for gestational age (SGA) seems to be a relevant risk factor for long‐term neurologic deficits. We compared the differences between amplitude‐integrated electroencephalography (aEEG) signals in very preterm infants born small for gestational age (SGA) and those in age‐matched infants born appropriate size for gestational age (AGA). Methods We performed serial aEEG recording on 305 infants: 255 (83.6%) were AGA, and 50 (16.3%) were SGA. Results The number of bursts per hour decreased over time in both groups, but was higher in the SGA group at every time point. On day one, it was significantly higher in the SGA group (17.4) than in the AGA group (10.1) (p = 0.016). The total Burdjalov score increased with post‐natal age and tended to be lower in SGA infants, but did not reach statistical significance at any time point. The percentage of continuous background patterns increased with post‐natal age in both groups, with no significant difference between the groups. Conclusion Very preterm infants born SGA showed normal maturation of aEEG signals during post‐natal life, but they also showed mild delays in electrocortical activity compared to age‐matched AGA infants. The predictive value of these findings on neurodevelopmental outcome needs to be further evaluated.